Comparative study of stress characteristics in surrounding bone during insertion of dental implants of three different thread designs: A three‐dimensional dynamic finite element study. Issue 1 (26th December 2018) - Udomsawat, Chaiwat; Rungsiyakull, Pimduen; Rungsiyakull, Chaiy; Khongkhunthian, Pathawee
Abstract: The objective of this study is to evaluate the stress distribution characteristics around three different dental implant designs during insertion into bone, using dynamic finite element stress analysis. Dental implant placement was simulated using finite element models. Three implants with different thread and body designs (Model 1: root form implant with three different thread shapes; Model 2: tapered implant with a double‐lead thread; and Model 3: conical tapered implant with a constant buttress thread) were assigned to insert into prepared bone cavity models until completely placed. Stress and strain distributions were descriptively analyzed. The von Mises stresses within the surrounding bone were measured. At the first 4‐mm depth of implant insertion, maximum stress within cortical bone for Model 3 (175 MPa) was less than the other models (180 MPa each). Stress values and concentration area were increasing whereas insertion depth increased. At full implant insertion depth, maximum stress level in Model 1 (35 MPa) within the cancellous bone was slightly greater than in Models 2 (30 MPa) and 3 (25 MPa), respectively. Generally, for all simulations, the highest stress value and the location of the stress concentration area were mostly in cortical bone. However, the stress distribution patterns during the insertion process were different between the models depending on the different designs geometry that contacted the surrounding bone. Different implant designs affect different stress generation patterns during implant insertion. A range of stress magnitude, generated in the surrounding bone, may influence bone healing around dental implants and final implant stability.